(1441) Structural changes of the Egyptian Balance of payment in the period 1960\61-1991\92 التغيرات الهيكلية في ميزان المدفوعات المصري في الفترة 1960/61-1991/92 - Saleh, Hussein Mohamed (The Institute of National Planning, 2018)
The developing countries are faced with a situation where there is a great disproportion between exports and imports. Therefore most of these countries are suffering deficits in their balances of current transactions.